(untitled) - Nijland, H. J. (Wageningen, Netherlands, 2005)
The main characteristic of this series is that the books are "practical" in the sense that they can be used in the day-to-day work of those professionals (mostly engineers) who are involved in irrigation and drainage.
Keywords: Subsurface drainage,Reclamation of land; Tiêu nước bề mặt